Lipoprotein(a) and Oxidized Phospholipids Promote Valve Calcification in Patients With Aortic Stenosis - Zheng, Kang H. (J Am Coll Cardiol, 2019)
BACKGROUND: Lipoprotein(a) [Lp(a)], a major carrier of oxidized phospholipids (OxPL), is associated with an increased incidence of aortic stenosis (AS). However, it remains unclear whether elevated Lp(a) and OxPL drive disease progression and are therefore targets for therapeutic intervention. OBJECTIVES: This study investigated whether Lp(a) and OxPL on apolipoprotein B-100 (OxPL-apoB) levels are associated with disease activity, disease progression, and clinical events in AS patients, along with the mechanisms underlying any associations. METHODS: This study combined 2 prospective cohorts and measured Lp(a) and OxPL-apoB levels in patients with AS (V(max) >2.0 m/s), who underwent baseline (18)F-sodium fluoride ((18)F-NaF) positron emission tomography (PET), repeat computed tomography calcium scoring, and repeat echocardiography. In vitro studies investigated the effects of Lp(a) and OxPL on valvular interstitial cells. RESULTS: Overall, 145 patients were studied (68% men; age 70.3 ± 9.9 years). On baseline positron emission tomography, patients in the top Lp(a) tertile had increased valve calcification activity compared with those in lower tertiles (n = 79; (18)F-NaF tissue-to-background ratio of the most diseased segment: 2.16 vs. 1.97; p = 0.043). During follow-up, patients in the top Lp(a) tertile had increased progression of valvular computed tomography calcium score (n = 51; 309 AU/year [interquartile range: 142 to 483 AU/year] vs. 93 AU/year [interquartile range: 56 to 296 AU/year; p = 0.015), faster hemodynamic progression on echocardiography (n = 129; 0.23 ± 0.20 m/s/year vs. 0.14 ± 0.20 m/s/year] p = 0.019), and increased risk for aortic valve replacement and death (n = 145; hazard ratio: 1.87; 95% CI: 1.13 to 3.08; p = 0.014), compared with lower tertiles. Similar results were noted with OxPL-apoB. In vitro, Lp(a) induced osteogenic differentiation of valvular interstitial cells, mediated by OxPL and inhibited with the E06 monoclonal antibody against OxPL. CONCLUSIONS: In patients with AS, Lp(a) and OxPL drive valve calcification and disease progression. These findings suggest lowering Lp(a) or inactivating OxPL may slow AS progression and provide a rationale for clinical trials to test this hypothesis.